New electropolymerizable metal-free and metallophthalocyanines bearing {2-[3-(diethylamino)phenoxy]ethoxy} substituents - KOCA, ATIF (ELSEVIER SCIENCE SA, 2014)
In this work, metal-free and metallophthalocyanines (Ni, Co, Cu) bearing peripherally tetra substituted 4-{2-[3-(diethylamino)phenoxy]ethoxy}groups were synthesized by cyclotetramerization of the corresponding phthalonitrile derivative and their electrochemical, spectroelectrochemical properties were investigated. Phthalocyanines were characterized by a combination of IR, H-1-NMR, UV-vis and MS spectral data. Diethylamino groups on the substituents of the complexes cause electropolymerization of the complexes on the working electrode during the oxidation reactions. Changing the potential window of the voltammetric cycles alters the electropolymerization mechanisms. Types of the metal center of the complexes also affect the electropolymerization mechanism. Spectroelectrochemical measurements were performed to assign the redox processes and spectroscopic responses of the electropolymerization processes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Synthesis; Diethylamino; Electropolymerization; Electrochemistry; Spectroelectrochemistry; ELECTROCHEMICAL PROPERTIES; PHOTOCHEMICAL PROPERTIES; SPECTROELECTROCHEMICAL CHARACTERIZATION; SPECTROSCOPIC CHARACTERIZATION; PULSE ELECTROPOLYMERIZATION; SOLUBLE PHTHALOCYANINES; CATALYTIC-ACTIVITY; COBALT; PORPHYRIN; ELECTRODE